PENGEMBANGAN CRITIKAL THINKING MAHASISWA MELALUI PENERAPAN PENDEKATAN INQUIRY PADA MATAKULIAH PENDIDIKAN SAINS - Widowati, Asri (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Critical thinking is an important matter and a vital topic in moderneducation. This ability is used in so many human life aspects. Thisability is seldom be learnt although it is including the part of science.The aim of this research is knowing development critical thinkingability of students through applying inquiry approach at ScienceEducation lecture.Research conducted with qualitative approach and strategy of thisresearch is by simulation observation. Subject of this research isBiological Education students. Data collected by using criticalthinking observation sheet. Existence of indication meaningfullearning is be expressed from learning process observation andexperiment report.Result of research indicate that the aspects of critical thinking can bedeveloped by applying inquiry approach. Some aspects of criticalthinking ability can be reached by student with good category, and theother aspects can be reached with good enough.